Programa Nacional de Fortalecimento da Agricultura Familiar (Pronaf): a questão do desenvolvimento rural - Xavier, Isabella Andrade Ferreira (2018)
If the State acts as an agent inside the struggle field of the social conflict, the decision about the creation of a program isn’t a simple concession of the State, but a measure that establishes itself due to a necessity, be it linked to a governmental program, be it to a social demand. However, the process involves interests and power disputes. Being its drawing the result of correlation of powers established in these disputes. Although some initial ideas of PRONAF didn’t seek to break with a model of agriculture already consolidated or that still retains a mercantile logic, the assertion of the family agriculture created new opportunities for a new range of public policies in Brazil. The objective of this work is the process of dispute that has established itself around PRONAF. The policy, by itself and new studies, enhancements, changes in benchmarks boosted by governmental changes has taken their own paths, consolidating, after twenty years of existence, as one of the most important public policies of the Brazilian rural milieu.